Dimensi Moral dalam Bentangan Filsafat dan Teori Hukum - Slamet Haryadi (KEADILAN PROGRESIF, 2012)
Expressing justice in law reality will never can penetrate sense of justice because life of construction have by modern life consequence which is materialistis and tend to do not want to strain after, paradigm of Positivism in the form of " modern law" legal of Menampakan character Positivistik. Moralitas to guide to action in role of judge, suggesting to human being to discontinue, to taking, revise and reorganize peran-2 which forming society in culture which is capitalist and materialistis and also not give assessment. Moral ideally earn critical merefleksi [of] problem punish which not be answered by modern law. To this is moral study become important discourse punish us is not platitude again. In Paradigm of Konstruktivisme which carrying Postmodernisme as resistance in philosophy of hermeneutika in the reality have trajectory with paradigm of Aristotellian about how its law [of] law, which both for giving justice.